PENGARUH KEPEMIMPINAN DAN REKRUTMEN TERHADAP KINERJA PEGAWAI PADA BIRO KESRA SEKRETARIAT DAERAH PROVINSI MALUKU - BATLAYERI, HERLINA BERTHA; TUANAYA, WAHAB (Patria Artha Management Journal, 2024)
The aim of this study was to examine and analyze the following aspects: the impact ofleadership on employee performance within the Bureau of Welfare of the RegionalSecretariat of Maluku Province; the effect of recruitment on employee performancewithin the same bureau; and the predominant influence of leadership and recruitment onemployee performance within the Bureau of Welfare of the Regional Secretariat ofMaluku Province. This research employed a quantitative approach, with a sample size of31 employees from the Bureau of Welfare. Data collection methods included observation,questionnaires, and documentation. Multiple linear regression analysis was utilized fordata analysis. Findings revealed that leadership significantly and positively influencesemployee performance. Leadership encompasses employees' characteristics, behaviors,and styles, which contribute to enhancing their performance. Recruitment also has asignificant and positive impact on employee performance, indicating the effectiveimplementation of recruitment procedures within the Kesra Bureau to hire skilledemployees. Furthermore, employee performance is notably and positively affected bydominant leadership, indicating that the leadership exhibited by employees during theirduties enhances performance within the Bureau of Welfare of the Maluku ProvinceRegional Secretariat. This leads to increased productivity, improved outcomes, timeefficiency, and cost-effectiveness.